Single-axis solar tracker / Dayang Nurasfarina Awang Sabaruddin - Awang Sabaruddin, Dayang Nurasfarina (2024)
The purpose of this study is to improvise a static solar panel to increase the power output from solar panels. This project is vital since the sun’s position will change throughout the time during the day, where it will move from the north to the west. Thus, having a static solar panel as a power generator will limit its function due to it wasn’t designed to move around and follow the sun’s position. The construction of this system used a Servo motor controlled by an Arduino microcontroller, which intelligently adjusts the prototype's position based on input from light-dependent resistor (LDR) sensors. In addition, the temperature sensor, DHT 11, also plays a part in this system which detects surrounding temperature and is expected to be displayed via a Wi-Fi module, on a device such as a computer or a smartphone. Another objective of producing this system is to encourage people especially electricity users to use solar energy as one of the power sources since it’s eco-friendlier and easier to get. The purposes of this study have been proven by several studies that have demonstrated that the proposed solar tracker successfully maximizes power output from solar panels.